Pelatihan Mitigasi Bencana Bagi Santri Pondok Pesantren Terpadu Darul Quran Mulia Bogor - Iswati, Heni; Rahmat, Hayatul Khairul; Wahyuningtyas, Ayu; Qodariah, Qodariah (Indonesian Journal of Emerging Trends in Community Empowerment, 2024)
Indonesia is a country prone to natural disasters, such as earthquakes, floods, landslides, tsunamis, and volcanic eruptions. Indonesia's geographical conditions located in the Pacific Ring of Fire and having a tropical climate make this country face continuous disaster risks. Therefore, disaster mitigation training is very important to provide understanding and skills to students so that they can act quickly and appropriately when a disaster occurs. Community service activities aimed at providing understanding and skills to students so that they can act quickly and appropriately when a disaster occurs can run smoothly and participants understand the material provided.